PURA KAJA SEGARA NIRMALA. Analogi Semiotik - Tumimbang, Trini N. A.; Surjono, .; Rate, Johannes Van (PS S1 Arsitektur. Jurusan Arsitektur, Fakultas Teknik Universitas Sam Ratulangi Manado, 2018)
Buildings are inanimate objects, but that doesn’t mean that these inanimate objects have no soul within. The soul of an object reflects through its image. An image designates a certain kind of view, a trace of appreciation that capture a meaning for someone. As a prospective architect, it’s our job to create and deliver an impression; beauty (an image) against a building. It should be natural that we design culturally; with consciousness and responsibility over a good usage of architectural language 3. Architecture that grows from religious appreciation is highly visible; how architecture in its true sense was inspired from the depths of human’s soul that susceptible with cosmological dimension 4. Those architectural practices can be seen in religious buildings such as Pura, a holy place and worship temple of Hindu Dharma in Indonesia. Being the oldest religion in the world, doesn’t mean that Hinduism is a rigid belief. But on the contrary, Hinduism is dynamic and flexible. Like the whelm of water, Hinduism is capable to adapt with environmental changes. In the Province of North Celebes, its Capital City, Manado, has 2.309 Hindustan and 3 praying temples, they are Pura Jagaditha that located in Taas (Tikala District), the Malalayang Hospital’s (at the hospital’s worship area) and the one that located in Karombasan, Wanea District. There are many kinds of Pura in Indonesia, however, the kind of Pura that will be discussed in this project is the one that closely related to water, Pura Segara. Semiotics analogy construe that a building is a sign of communication (to convey an information) about what it really is and what does it do. Architecture is not a meaningless expression, and also it isn’t just one meaning. An expression of architectural language can be found in form, space and order of the design’s particularity. This analogical method is suitable for this object where every aspects of the design such as location, orientation, shape, room and even structure, they all must follow the rules so that everything becomes meaningful.Keywords : Semiotics, Analogy, Pura, Segara, Hindu Dharma